Stereotactic radioablation of ventricular arrhythmias in patients with structural heart disease – A systematic review. (September 2021) - Kovacs, Boldizsar; Mayinger, Michael; Schindler, Matthias; Steffel, Jan; Andratschke, Nicolaus; Saguner, Ardan M.
Highlights: Systematic review of stereotactic arrhythmia radioablation to treat ventricular arrhythmias. Safety of radioablation in selected patients with structural heart disease could be demonstrated. Short-term reduction in ventricular arrhythmia burden is pronounced, but recurrences are common. High recurrence rate could be related to low radiation dose applied in all investigated patients. Abstract: Background and purpose: Several studies have suggested stereotactic arrhythmia radioablation (STAR) as a treatment option for patients suffering from therapy-refractory ventricular tachycardia or fibrillation (VT/VF). Material and methods: We performed a systematic review of human reports of STAR for structural VT/VF to assess its effectivity and safety. All identified publications were assessed for inclusion. This study adheres to the PRISMA guidelines and was registered on PROSPERO (CRD42020183044). Results: Thirteen studies were included resulting in a population of 57 patients. Median age was 64 (range 34–83), 31 patients (54%) had ischemic cardiomyopathy and 50 patients (88%) had prior catheter ablation (CA) for VT/VF. A mean planned target volume of 64.4 cc (range 3.5–238) with a mean safety margin of 3.3 mm (0–5) was treated with 25 Gy. Immediately following STAR, four patients (7%) experienced an electrical storm. During a mean follow-up duration of 410 days, all patients suffering from sustained VT/VF prior to STAR ( n  = 55) had a reduction of their sustained VT/VF-burden after STAR, but recurrence occurred in 41 patients (75%) during follow-up. Forty-six patients (81%) had an adverse effect from therapy, but no treatment-related death occurred. Evidence of scar-formation after STAR either by imaging, invasive mapping or histopathology was found in six of nine examined patients (67%). Conclusion: From the still very limited experience, STAR appears effective and safe in patients with structural heart disease and therapy-refractory sustained VT/VF. It is associated with a significant short-term reduction of sustained VT/VF-burden, but recurrences are common.